Melacak Jejak Hermeneutika Fazlur Rahman dalam Wacana Teori Tafsir: Perspektif Historis dan Epistemologis - Rahmawati, Rahmawati; Muhtolib, Muhtolib (STAINI Press, 2024)
The development of the theory of Qur'anic interpretation in the realm of contemporary Islamic thought shows an increasingly urgent methodological need to bridge the gap between the sacred text and the ever-changing social reality. In the midst of this dynamic, the hermeneutical approach offered by Fazlur Rahman, especially the double movement theory, is present as a methodological offering that attempts to reconstruct the way of viewing the text of the Qur'an ethically and historically. This study aims to trace the intellectual trail of Fazlur Rahman's hermeneutics in the development of contemporary interpretation theory by highlighting the historical and epistemological dimensions of his thinking. The method used in this study is a qualitative study based on literature study, with a historical-critical approach and discourse analysis. Primary and secondary sources related to Fazlur Rahman's works and the responses of contemporary Muslim intellectuals are the focus of the analysis. The results of the study show that Fazlur Rahman's double movement theory not only represents a synthesis between textual and contextual understanding, but also provides an epistemological foundation for the development of a more dialogical, transformative, and contextual interpretation theory. The implications of these findings indicate the need for revitalization of the tafsir approach that is not only rooted in the classical heritage, but also open to social dynamics and universal ethical values. This research also opens up space for the development of maqāṣid-based tafsir theory that can respond to the needs of contemporary Muslim society more inclusively.